Implementation of Environmental Accounting in Achieving Social Responsibility at Tourist Attractions in Bandar Lampung - Putri, Rosydalina; Saputra, Muhammad (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research was motivated by the author's desire to study environmental accounting at Batu Putu Bandar Lampung tourist attraction. Tourist Attractions in Bandar Lampung are experiencing rapid progress, this is evidenced by data from the City Government of Bandar Lampung which states the continued increase in the number of visitors or tourists who come. Along with the increase in the number of tourists it raises the question of whether the company is responsible for the environment around the attraction. The problem formulated in this study is how to implements environmental accounting in Batu Putu tourist attraction, then how the methods used in the recognition of environmental costs and what social responsibility looks like. The study had 6 samples that were considered to meet the criteria. The method used is qualitative analysis by data collection through interviews and observations. The results obtained in this study are some companies have implemented cost accounting with PSAK-appropriate methods and have contributed to realizing social responsibility.